Library news trends in national digital media - Yesi Melda; Nining Sudiar; Eko Noprianto (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. Library coverage in digital media reflects public attention to library development. This study examines trends in library news coverage in national digital media focusing on volume, topics, library types, tone, geographic location, and photo usage. Research Methods. A quantitative descriptive approach with content analysis was applied to 511 news articles published by Detik.com, Kompas.com, Tribunnews.com, CNNIndonesia.com, and Liputan6.com from January 2023 to December 2024. The unit of analysis consisted of news articles focusing primarily on libraries. Data Analysis. The analysis focused on the content and context of library reporting. Results. The findings show that themes of services, literacy activities, and facility development dominated coverage. Public libraries appeared most frequently, while community and mobile libraries received limited attention. The overall tone was predominantly positive, with coverage concentrated in urban areas, particularly DKI Jakarta. Most articles included photos to reinforce visual messages. Conclusion. Digital media portrays libraries as progressive and relevant institutions, highlighting the need for more structured publication strategies and broader coverage to ensure balanced representation.